THE LEGAL POSITION OF WORKERS AS PREFERRED CREDITORS WHO BECOME THE APPLICANT FOR BANKRUPTCY AGAINST THE COMPANY - Wijayati, Ani; Nainggolan, Anton; Krisnawati, Yessi Melati (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2021)
This study aims to trace the contradictions of sentencing arrangements in child sexual abuse crimes in Aceh after the enactment of Qanun No. 6 of 2014 with Law No. 35 of 2014 on Child Protection. The regulation of child sexual abuse punishment in jinayat law in Aceh has different interpretations from other laws and regulations, including Law No. 35 of 2014 on Child Protection. So the essence of the deterrent effect for perpetrators that should be part of the goal of criminalization is not so achieved. In addition, Qanun Jinayat also has the potential for impunity for the government with Article 9 and Article 11 Qanun No. 6 of 2014 on the reasons for justification and forgiving reasons. The method used in this paper is a normative juridical method, using secondary data or library data. The study results showed that in Aceh, there had been a dualism of the legal regulation of child sexual abuse. The provisions of qanun jinayat are still many shortcomings in providing protection and rights for children as victims, so law enforcement tends to choose positive laws. It is recommended that the Aceh government to harmonize the law between jinayat law provisions and positive laws relating to sexual harassment.